Абсолютное бытие как цель и смысл человеческого существования - Астапов, Сергей Н. (Autor, 2017)
Artykuł jest poświęcony analizie rozstrzygnięcia pytania o sens ludzkiej egzystencji przez założenie bytu absolutnego. Artykuł uzasadnia tezę: jeśli cel, a zatem sens pochodzi od konkretnej sytuacji człowieka, zestaw wyników „sytuacyjnej egzystencji”, osobnych, a czasami nawet sprzecznych, nie pozwalają nam mówić o konkretnej ludzkiej egzystencji. Jeżeli dana osoba widzi sens swojego istnienia w bycie absolutnym, jego celem jest osiągnięcie pełni bytu, który jest dobrem absolutnym.

The article is devoted to analysis of the issue on meaning of human existence and its solution through statement on the absolute being. The article justifies the thesis: if the goal, and therefore the meaning derives from a concrete human situation, the set of results of “situational existence”, separate and sometimes even contradictory, do not allow us to speak about a concrete human existence. If an individual sees meaning of his existence in the absolute being, then he purposes to realize completeness of being which is the absolute good.
Istnienie absolutne jako cel i sens ludzkiej egzystencji
Keywords: абсолютное бытие; смысл жизни; цель; русская религиозная философия; ценности; bycie absolutne; sens życia; cel; rosyjska filozofia religijna; wartości; absolute being; meaning of life; purpose; Russian religious philosophy; values